Synthesis and Characterization of Fe-doped Hydroxyapatite/ZnO Nanocomposites Using the Coprecipitation Method from Processed Limestone - Arie Hardian; Rosalinawati Dewi; Jasmansyah Jasmansyah; Dani Gustaman Syarif; Anceu Murniati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Hydroxyapatite (HAp) is the main inorganic component that forms teeth and bones. The abundant limestone reservoir in Indonesia can be utilized as a natural resource for the green synthesis of hydroxyapatite. The objective of synthesizing Fe-doped hydroxyapatite/ZnO nanocomposites is to enhance the magnetic properties of hydroxyapatite, facilitating its utilization as a biomaterial in drug delivery systems. This application proves valuable in regulating the timing and location of active substance decay in pharmaceuticals. The coprecipitation method was employed to synthesize Fe-doped hydroxyapatite (Fe-HAp) at varying concentrations of 0%, 2.5%, 5%, and 10% mol. Subsequently, Fe- HAp/ZnO nanocomposites were crafted with a weight ratio 4:1 through straightforward homogenization between nano Fe-HAp and nano ZnO, utilizing ethanol as a solvent. The analytical tools employed for characterization included X-ray fluorescence (XRF), X-ray diffraction (XRD), and Vibrating Sample Magnetometer (VSM). XRF analysis revealed that the Ca/P ratio in the Fe- HAp/ZnO nanocomposite decreased with increasing Fe dopant concentration, while the weight percentage of ZnO remained consistent across all nanocomposites. The XRD results demonstrated the presence of typical diffraction patterns of HAp and ZnO in the Fe-HAp/ZnO nanocomposite. However, secondary phases such as β-TCP, CaCO3, and Fe2O3 were observed in the Fe-HAp sample. The crystallite size of the Fe-HAp/ZnO nanocomposite generated in this study ranged from 29 to 38 nm. VSM characterization outcomes indicated that the substitution of Fe(III) can modify the diamagnetic properties of hydroxyapatite, rendering it ferromagnetic or superparamagnetic, depending on the dopant concentration employed.